1992
DOI: 10.1007/bf00210770
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant congenital cataract and microphthalmia associated with a familial t(2;16) translocation

Abstract: We describe a family in which autosomal dominant congenital cataract and microphthalmia were segregating together with a reciprocal translocation t(2;16) (p22.3;p13.3) through three generations. This family included four individuals with balanced translocations, three with partial trisomy 2p derived from this translocation, and two with a normal karyotype. All of the subjects with balanced and unbalanced translocations had congenital cataract and microphthalmia, whereas the two individuals with normal karyotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 3 publications
1
23
0
Order By: Relevance
“…Scale bar, 20 mm. t(2;16)(p22.3;p13.3) translocation [Yokoyama et al, 1992]. A further patient with congenital cataract associated with a ring chromosome 16 has also been described [He and Li, 2000], implicating the 16p13.3 region in cataract causation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Scale bar, 20 mm. t(2;16)(p22.3;p13.3) translocation [Yokoyama et al, 1992]. A further patient with congenital cataract associated with a ring chromosome 16 has also been described [He and Li, 2000], implicating the 16p13.3 region in cataract causation.…”
Section: Discussionmentioning
confidence: 93%
“…The 16p13.3 breakpoint lies in a region known to harbor a cataract locus (MIM] 156850) [Yokoyama et al, 1992]. In addition, a patient with congenital cataracts is reported with a ring chromosome 16 [He and Li, 2000].…”
Section: Translocation Breakpoint Analysismentioning
confidence: 98%
“…This autosomal dominant disorder was mapped to 16p13.3 in a Japanese family in which affected members had a familial t(2;16) translocation (Yokoyama et al, 1992), and it was suggested that a gene involved in eye development may be disrupted by the translocation. In view of the role of the D. melanogaster sol gene in visual system development and the conservation of the gene between D. melanogaster and human, SOLH is a candidate gene for this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…We have mapped SOLH to the short arm of human chromosome 16, at band p13.3. It has been suggested that CATM (hereditary cataracts with microphthalmia) is in this region following the discovery of a t(2;16) translocation in an affected family (Yokoyama et al, 1992). SOLH is therefore a candidate gene for this developmental disorder of the human visual system.…”
Section: Introductionmentioning
confidence: 99%
“…Yunis, 1978Neu et al, 1979E. Yunis et al, 1979Kishi et al, 1980Nagano et al, 1980Say et al, 1980Monteleone et al, 1981 Larson et al, Larson et al, 1982Larson et al, 1982Larson et al, 1982Larson et al, 1982Mitsudo et al, 1982Rosenfeld et al, 1982Fineman et al, 1983Fineman et al, 1983Fineman et al, 1983Schober et al, 1983Walbaum et al, 1984Bridge et al, 1985Niebuhr et al, 1985 Wakita et al, Fryns et al, 1986Pueschel et al, 1987Singer et al, 1987Vianello et al, 1988 Fryns et al, Parruti et al, 1989Heathcote et al, 1991Sarda et al, 1992Yokoyama et al, 1992Magee et al, 1994Sawyer et al, 1994 Our case 1 Our case 2 Our case 3…”
Section: Clinical Reportsmentioning
confidence: 96%